2008
DOI: 10.1143/apex.1.104001
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Nano-Catalyst Particles by Spinodal Nano-Decomposition in Perovskite

Abstract: A new mechanism of nano-catalyst generation based on the spinodal nano-decomposition in self-regenerating perovskite catalysts for automotive-emissions control is proposed. To demonstrate existence of the spinodal nano-decomposition in real perovskite catalysts, we performed first-principles calculations to evaluate the free energy of La(Fe 1−x Pd x )O 3 and La(Fe 1−x Rh x )O 3 . The result indicates appearance of a spinodal region in the phase diagram of each material. Formation of nano-catalyst particles in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 29 publications
4
25
0
Order By: Relevance
“…According to previous investigations of perovskite‐supported precious metal systems, a possible mechanism including the rapid diffusion of the metal,5a the nanoscale spinodal decomposition,5g and the generation of surface phases5c might account for the cyclical re‐dispersion function observed here. The diffusion of metallic Ni particles is expected for a host perovskite with a large cell volume and sufficient structural defects.…”
supporting
confidence: 60%
“…According to previous investigations of perovskite‐supported precious metal systems, a possible mechanism including the rapid diffusion of the metal,5a the nanoscale spinodal decomposition,5g and the generation of surface phases5c might account for the cyclical re‐dispersion function observed here. The diffusion of metallic Ni particles is expected for a host perovskite with a large cell volume and sufficient structural defects.…”
supporting
confidence: 60%
“…As one more example of possible functionalities worth mentioning is the case of catalysts for automotive-emissions control. Here, by using decomposed alloy with spatially separated NCs containing the relevant metal, e.g., Pt, the destructive process of metal agglomeration could be much reduced (Hamada et al, 2011;Katz et al, 2011;Kizaki and Katayama-Yoshida, 2013;Kizaki et al, 2008).…”
Section: Prospects Of Spinodal Nanotechnologymentioning
confidence: 99%
“…These materials are of great interest for methane steam reforming and methane dry reforming reactions due to their resistance to sintering and the decreased formation of carbonaceous deposits. 16,28,30 The reactivity of AB 2 O 4 /ABO 3 materials has been ascribed to many mechanisms: ability of individual atoms within the bulk structure to move reversibly in and out lattice, 16,23 nanospinodal decomposition, 24,39 reactivity of oxygen contained within the material, 15,18,22,27,28,31,34 formation of metal nanoparticles within the bulk structure framework, 8,9,19,30,40,41 or formation of nickel oxide particles supported by the nickel aluminate structure. 20 Several methods are commonly used to prepare mixed oxide catalysts: solid state reaction, 35 co-precipitation, 6,14,31,42,43 sol-gel method, 13,20,44 combustion synthesis, 19 alkoxide method, 17,18,24 and Pechini synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that Pd was able to move out of the perovskite lattice under reducing conditions and back in its original position in an oxidizing atmosphere giving it high catalytic activity and a long lifetime. In a separate study by Kizaki et al, La(Fe 1-x Pd x )O 3 perovskites prepared by the alkoxide method were found to have excellent stability and activity for automotive emissions control due to nanospinodal decomposition 24. In nanospinodal decomposition, the perovskite decomposes into LaFeO3 and PdFeO 3 at high temperatures, but the crystal structure itself is maintained.…”
mentioning
confidence: 99%